Purine salvage enzymes as targets for the chemotherapeutic treatment of parasitic diseases - Craig, S. (Биополимеры и клетка, 1994)
The review analyses the results showing that technological advances in studying the specific target molecules in a cell allow to develop new effective drugs for the treatment of a number of human maladies. The new approach to the drug design is based In the data of enzyme structure. В огляді проаналізовано результати, які показують, що досягнення у вивченні специфічних молекул-мішеней клітини дозволяють розробляти ефективні лікарськи засоби для лікування багатьох захворювань людини. Встановлено, що новий підхід до розробки таких медикаментів базується на дослідженні структури молекули фермента. Обзор анализирует результаты, показывающие, что достижения в изучении специфических молекул-мишеней клетки позволяют разрабатывать эффективные лекарственные средства для лечения многих заболеваний человека. Установлено, что новый подход к разработке таких медикаментов основан на исследовании структуры молекулы фермента.